Peran Humas KPU dalam Program Sosialisasi Pendidikan Pemilih Pada Pilkada 2024 - Hasna Nuha Tsabitah; Asri Pratiwi Tenggara; Fadhilah Zahrah Based; Winda Dwi Astuti Zebua (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The regional head election (Pemilukada) in Indonesia is an important part of the democratic process, which will be held simultaneously on November 27, 2024. This event involves all elements of society in determining regional leaders, including governors, regents, and mayors. The General Election Commission (KPU) plays the role of an independent and neutral organizer, responsible for ensuring that the election is conducted fairly and democratically. In an effort to increase public participation, the KPU implements the Voter Education Socialization program, which aims to provide understanding of the importance of Pemilukada, the voting process, and citizens' responsibilities. This study employs a qualitative approach with library research methods to explore the role of KPU's Public Relations in this socialization program. The findings indicate that the KPU has successfully raised awareness and participation among the public through various communication strategies, including the use of social media and direct activities. Although there has been a decline in voter participation compared to the previous presidential election, this socialization program is expected to strengthen community engagement in the 2024 Pemilukada. This research contributes to the literature on the role of KPU's Public Relations in creating a society that is aware of the importance of elections, particularly in the context of the 2024 Pemilukada